Validation of the Low-Frequency Procedure for Field Measurement of Façade Sound Insulation - Jinyu Liu; Naohisa Inoue; Tetsuya Sakuma (Buildings, 2021)
In the ISO 16283 series for field measurement of sound insulation, a low-frequency procedure is specified for determining indoor average sound pressure level, which is the so-called corner method. In the procedure, additional measurements are required in the corners in addition to the default measurements in the central zone, and the indoor average level is corrected with the highest level in the corners. However, this procedure was empirically proposed, and its validity is not fully examined for façade sound insulation. In this paper, detailed experiments were performed in a mock lightweight wooden house for validating the low-frequency procedure for façade sound insulation measurement. The results suggest that a correction with energy-averaging level of all corners is more reliable than with the maximum level, and the uncertainty in the default procedure is sufficiently improved with additional measurements in four non-adjacent corners. Moreover, the effect of the detailed position of the microphone around the corner was clarified for a more specific instruction.